Succinate production positively correlates with the affinity of the global transcription factor Cra for its effector FBP in Escherichia coli. Issue 1 (December 2016) - Wei, Li-Na; Zhu, Li-Wen; Tang, Ya-Jie
Abstract Background Effector binding is important for transcription factors, affecting both the pattern and function of transcriptional regulation to alter cell phenotype. Our previous work suggested that the affinity of the global transcription factor catabolite repressor/activator (Cra) for its effector fructose-1, 6-bisphosphate (FBP) may contribute to succinate biosynthesis. To support this hypothesis, single-point and three-point mutations were proposed through the semi-rational design of Cra to improve its affinity for FBP. Results For the first time, a positive correlation between succinate production and the affinity of Cra for FBP was revealed inEscherichia coli . Using the best-fit regression function, a cubic equation was used to examine and describe the relationship between succinate production and the affinity of Cra for FBP, demonstrating a significant positive correlation between the two factors (coefficient of determinationR 2 = 0.894, P = 0.000 < 0.01). The optimal mutant strain was Tang1683, which provided the lowest mutation energy of −4.78 kcal/mol and the highest succinate concentration of 92.7 g/L, which was 34% higher than that obtained using an empty vector control. The parameters for the interaction between Cra and DNA showed that Cra bound to the promoter regions ofpck andaceB to activate the corresponding genes. Normally, Cra-regulated operons under positive control are deactivated in the presence of FBP. Therefore, theoretically, the enhanced affinity of Cra for FBP will inhibit the activation ofpck andaceB . However, the activation of genes involved in CO2 fixation and the glyoxylate pathway was further improved by the Cra mutant, ultimately contributing to succinate biosynthesis. Conclusions Enhanced binding of Cra to FBP or active site mutations may eliminate the repressive effect caused by FBP, thus leading to increased activation of genes associated with succinate biosynthesis in the Cra mutant. This work demonstrates an important transcriptional regulation strategy in the metabolic engineering of succinate production and provides useful information for better understanding of the regulatory mechanisms of transcription factors.